Updated spatial distribution and health risk assessment of heavy metals in soils of the Yangtze River Basin, China - Sun, Yifan; Liu, Dongsheng; Wu, Yuanzhu; He, Xiaowei; Luo, Yang; Zhou, Xiaoguo; Chen, Wenran; Chen, Wei; Li, Sen (Frontiers in Environmental Science, 2023)
Supporting ecological protection and restoration has been at the heart of China's ambitious Yangtze River conservation strategy. Knowledge of the current status of heavy metal distribution is important for planning remediation practices and allocation to waste treatment facilities. Through an extensive and systematic review of literature, this study depicts the up-to-date spatial distribution and characteristics of typical heavy metals in soils in the Yangtze River Basin, China. A total of 7694 geo-referenced records of heavy metal in soils of the Yangtze River Basin were compiled from the literature published between 2000 to 2020. The results show a spatially-heterogeneous concentrations of Zn, Cu, Pb, Cr, Ni, As, Hg and Cd. The degree of heavy metal pollution was relatively higher in the middle reaches, while it was relatively lower in the upstream and downstream. According to the limits set by the state to ensure agricultural production and maintain human health, the average concentration of Cd greatly exceeded its limit. Overall, a certain number of heavily polluted areas were found to occur in regions with frequent human economic activities, posing potential health risks. The carcinogenic and non-carcinogenic risks of children are 1.4 times and 1.6 times higher than those of adults, respectively, and the heavy metal with the highest risk to human health was Cr. This study provides an important basis for the field of soil pollution prevention and control in the Yangtze River Basin. It updates the current understanding of the spatial pattern of major pollutants in a large ecologically protected region in China, which is conducive to the precise prevention and control of public health risks.